Non-Mulberry and Mulberry Silk Protein Sericins as Potential Media Supplement for Animal Cell Culture. (19th July 2016) - Sahu, Neety; Pal, Shilpa; Sapru, Sunaina; Kundu, Joydip; Talukdar, Sarmistha; Singh, N. Ibotambi; Yao, Juming; Kundu, Subhas C.
Abstract : Silk protein sericins, in the recent years, find application in cosmetics and pharmaceuticals and as biomaterials. We investigate the potential of sericin, extracted from both mulberry Bombyx mori and different non-mulberry sources, namely, tropical tasar, Antheraea mylitta ; muga, Antheraea assama ; and eri, Samia ricini, as growth supplement in serum-free culture medium. Sericin supplemented media containing different concentrations of sericins from the different species are examined for attachment, growth, proliferation, and morphology of fibrosarcoma cells. The optimum sericin supplementation seems to vary with the source of sericins. The results indicate that all the sericins promote the growth of L929 cells in serum-free culture media; however, S. ricini sericin seems to promote better growth of cells amongst other non-mulberry sericins.